Evidence Assessment of the Criminalisation of the Purchase of Sex: A Review - Forbes, Emma (2017)
The report provides a rapid evidence assessment of available evidence on the impact of the criminalisation of the purchase of sex and examines existing international evidence which draws predominantly on countries where legislation criminalising the purchase of sex exists